Response of Gait Output and Handgrip Strength to Changes in Body Fat Mass in Pre- and Postmenopausal Women - Sam Ibeneme, BMRPT, MSc, PhD; Chinenye Ezeigwe, BMRPT; Georgian C. Ibeneme, BNSc, MSc; Amarachi Ezuma, BMRPT; Ifeoma Okoye, MBBS; Joseph M. Nwankwo, BPhysio, MBBS, MSc, PhD (Elsevier, 2019)
Background: Available preliminary data on menopause does not relate changes in body fat mass (BFM) and handgrip strength (HGS) (an indicator of body/muscle strength) to gait parameters. Objective: To determine the relationship between BFM, HGS and gait parameters, namely, stride length (SL) (an indicator of walking balance/postural stability), stride frequency (SF), and velocity (V) (gait output), to guide gait training. Methods: Ninety consenting (45 postmenopausal and 45 premenopausal) female staff of the University of Nigeria Teaching Hospital, Enugu, were randomly selected and assessed for BFM and HGS with a hydration monitor and dynamometer, respectively, in an observational study. The mean of 2 trials of the number of steps and time taken to cover a 10-m distance at normal speed was used to calculate SF, SL, and V. Data were analyzed using an independent t test and a Pearson correlation coefficient at P < 0.05. Results: Premenopausal (BFM = 42.93% [12.61%], HGS = 27.89 [7.52] kg, stride ratio = 1.43, and velocity = 1.04 [0.01] m/sec) and postmenopausal (BFM = 41.55% [12.71%], HGS = 30.91 [7.07] kg, stride ratio = 1.44, and velocity = 1.06 [0.01] m/sec) women showed no significant differences in gait output/velocity (t = 0.138; P = 0.89; d = 0.029). At postmenopause, BFM was significantly and negatively (r = -0.369; r2 = 0.1362; P = 0.013) correlated with SL, whereas HGS was positively and significantly (r = 0.323; r2 = 0.104; P = 0.030) correlated with gait output at premenopause. Conclusions: BFM may adversely influence walking balance at postmenopause, whereas HGS may enhance gait output at premenopause but not postmenopause. Therefore, muscle strengthening alone may not enhance gait output in postmenopausal women without balance training. Key words: body fat mass, gait output, hand grip strength, menopause, stride ratio